2014
DOI: 10.1074/jbc.m113.514810
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Dynamics of Annexin A6 Trigger Feedback Regulation of Hypertrophy via Atrial Natriuretic Peptide in Cardiomyocytes

Abstract: Background: Altered annexin A6 expression is associated with several cardiovascular disorders, including myocyte hypertrophy, but precise functions of the protein remain elusive. Results: Dynamic association of annexin A6 with intracellular atrial natriuretic peptide precursor protects against adrenergic stimulation-induced hypertrophy of H9c2 cardiomyocytes. Conclusion: Annexin A6 negatively regulates hypertrophic progression of cardiomyocytes. Significance: Annexin A6 exhibits potential for antihypertrophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 60 publications
(37 reference statements)
2
15
0
Order By: Relevance
“…Phenylephrine (PE from Sigma) dissolved in sterile water, bezafibrate and fenofibrate (from Sigma) dissolved in di-methyl sulfoxide (DMSO) were used for treatment in cell culture. Several earlier studies showed that 100 µM PE in 24 hours caused hypertrophy of cardiomyocytes in vitro [21,[25][26][27]. Therefore, in the present study, hypertrophy in H9c2 cardiomyocytes was induced by treatment with 100 µM PE for 24 hours.…”
Section: Methodsmentioning
confidence: 50%
See 1 more Smart Citation
“…Phenylephrine (PE from Sigma) dissolved in sterile water, bezafibrate and fenofibrate (from Sigma) dissolved in di-methyl sulfoxide (DMSO) were used for treatment in cell culture. Several earlier studies showed that 100 µM PE in 24 hours caused hypertrophy of cardiomyocytes in vitro [21,[25][26][27]. Therefore, in the present study, hypertrophy in H9c2 cardiomyocytes was induced by treatment with 100 µM PE for 24 hours.…”
Section: Methodsmentioning
confidence: 50%
“…The spatial increase in cell size was analyzed by AFM of fixed cells as reported earlier with minor modifications [25]. Briefly, H9c2 cardiomyocytes were pretreated with or without 10 µM fenofibrate and incubated in the presence of 100 µM PE for 24 hours.…”
Section: Monitoring Cellular Hypertrophy By Atomic Force Microscopy (mentioning
confidence: 99%
“…Confocal imaging was performed on a TCS-SP8 platform (Leica Microsystems) equipped with ×63/1.4 NA oil, ×63/1.2 NA water, or ×40/1.2 NA oil objectives; 405/488/561/633 nm laser lines; and photomultiplier and hybrid (Leica HyD) detector systems. Highresolution images were acquired as described elsewhere (57,66). For faster time-lapse imaging, an 8K resonant scanner was used.…”
Section: Discussionmentioning
confidence: 99%
“…Stained cells were visualized under a TCS SP8 confocal microscope (Leica Microsystems, Wetzlar, Germany) using a 63 × 1.4 numerical aperture oil objective. High-resolution images were acquired as described elsewhere54. Images were deconvolved, and colocalization was analyzed using Huygens Professional software (Scientific Volume Imaging B.V., Hilversum, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%